The Involvement of DNA Methylation and Histone Modification on the Epigenetic Regulation of Embryonic Stem Cells and Induced Pluripotent Stem Cells - Siu-Sing Leung, Kenneth; Wing-Sang Cheng, Vincent; Wing-Fai Mok, Simon; Kwok-Wing Tsui, Stephen (Current Stem Cell Research & Therapy, 2014)
Stem cell research has been developing rapidly in diverse areas such as the fields of genetics and molecular biology over the past decades. Genomic studies on both embryonic stem cells (ESCs) and terminally-differentiated cells illustrated that factors apart from their hereditary information disparity are associated with gene expression patterns of ESCs. Therefore, current research is trying to explore the effects of epigenetic processes in stem cell physiology and phenotypic changes. In-depth analyses of the molecular mechanisms underpinning such epigenetic-mediated functions have also been conducted. These findings suggest the importance of understanding the epigenetic influences in stem cell activities. Accordingly this review will describe the regulatory machineries of stem cells development targeting the two epigenetic processes: (1) DNA methylation and (2) histones modification. In addition, up-to-date findings concerning the functional roles of these processes in stem cells homeostasis will be covered.
Keywords: histones modifications